Maternal perspectives on preschoolers’ negative emotions and their emotional social competence - Hà, Phạm-Thị (2021)
In this study, the relationship between mothers’ self-reported responses to preschoolers’ negative emotions and maternal perceptions of the children’s social emotional competence was first investigated with Vietnamese mothers, whose children were 2 to 6 years old. The research also examined the influences of parent background variables and their responses to young children’s undesirable emotions on their awareness of children’s social emotional skills. The data are collected from an online survey using adapted Coping with Negative Emotions Scale (CCNES) (focusing on anger, sadness, fear and anxiety) and Strengths and Difficulties Questionnaire (SDQ). The findings from correlation analysis showed that mothers’ minimizing or encouraging emotional expression did not have any connection with children’s prosocial behaviours, which were positively and significantly related to emotion-focused and problem-focused reactions, while all non-supportive responses from mothers were significantly and positively correlated with children’s problems. Furthermore, the results from hierarchical multiple regression analyses indicated that preschoolers' reported social emotional competence were positively affected by their mothers’ problem-focused reactions, while their reported difficulties were negatively predicted by grandparents’ influences but positively by mothers’ job dissatisfaction and punitive reactions to their fear, sadness, anxiety and anger.